UPAYA GURU MENANGGULANGI DYSARTHRIA MELALUI METODE BERNYANYI PADA KELOMPOK BERMAIN - Dwiyani Anggraeni (LPPM IAD Probolinggo, 2024)
Children aged 4–6 years are in the preschool stage, which is a crucial period in language development. At this stage, children's language skills develop rapidly, marked by increased fluency and vocabulary. However, disorders in this system can cause obstacles to language development, one of which is dysarthria. Dysarthria is a speech disorder that affects articulation skills, making it difficult for others to understand what the sufferer says. This condition can hinder communication and impact children's self-confidence and social skills. This study aims to describe the use of singing methods to help overcome dysarthria in early childhood. The method used is a qualitative descriptive study with data collection techniques in the form of observation, interviews, and documentation. The singing method was chosen because it can provide enjoyable stimulation and train children's articulation, pronunciation, and speech motor coordination skills. The results of the study indicate that the application of the singing method can help improve the speech skills of children with dysarthria. Through singing activities, children become more active, confident, and able to pronounce words more clearly. Thus, the singing method can be an effective learning alternative to help overcome dysarthria in early childhood.